Factor that affects delay schedule performance of construction project - Zulkifli, Nur Afiqah; Omar, Siti Nur Zahirah; Setapa, Mariam (International Journal of Accounting, Finance and Business, 2025)
Delays in construction projects are a pervasive issue that significantly impacts project performance. This study aims to identify and analyse the critical factors contributing to construction delays across different global regions. Employing a systematic literature review, we analysed data from 33 studies conducted in Africa, Western Asia, Eastern Asia, Southern Asia, South/North America, and globally. The review process began with the identification of key concepts and topics related to construction delays. Searches were conducted in Scopus and Google Scholar, focusing on articles published between 2019 and 2023. Advanced search techniques yielded an initial pool of 87 papers, which was refined to 33 relevant papers for detailed analysis using NVivo software. The results key delay factors identified include management and performance, resources availability, communication and coordination, financial uncertainties, and planning and scheduling. Significant regional variations were observed in the emphasis placed on different delay factors. In conclusion, understanding the multifaceted causes of project delays is crucial for enhancing project management practices and ensuring timely project delivery. This study provides valuable insights into regional differences in the study of construction delays, emphasising the need for targeted strategies to address these issues effectively. The findings aim to contribute to the global improvement of project management practices by identifying and mitigating critical delay factors in construction projects.